Cancer-associated fibroblasts-derived exosomal piR-35462 promotes the progression of oral squamous cell carcinoma via FTO/Twist1 pathway - Yushan Ye; Fan Wu; Bowen Li; Hanyu Ma; Lianxi Mai; Yu Peng; Xiaodi Feng; Xiao Tan; Min Fu; Yongmei Tan; Tianjun Lan; Ruixin Wang; et al. (BMC Oral Health)
Abstract Background Cancer-associated fibroblasts (CAFs) represent a crucial component of tumor stroma and play critical roles in cancer progression. However, the role of CAFs derived exosomes in oral squamous cell carcinoma (OSCC) environment is unexplored. PIWI-interacting RNAs (piRNAs) serve as epigenetic effectors in cancer progression and constitute significant compositions of exosomes. Here, we explored the functional mechanism of exosomal piRNAs in OSCC development. Methods We screened exosomal piRNAs derived from CAFs and normal fibroblasts (NFs) and assess their effect on tumor proliferation and metastasis. A nude mouse model was established to assess the impact of exosomal piR-35462 on tumor progression. Results CAFs-derived exosomes showed an enhanced piR-35462 expression and promoted OSCC cell proliferation, migration and invasion. Additionally, elevated piR-35462 expression in OSCC tissues correlates with poor prognosis. Mechanistically, CAFs-derived exosomal piR-35462 increased the expression of fat mass and obesity-associated protein (FTO) in OSCC cells. By inhibiting N6-methyladenosine (m6A) RNA methylation, the overexpression of FTO further enhances the stability and expression levels of Twist1 mRNA, thereby contributing to epithelial-mesenchymal transition (EMT) and tumor progression. In vivo xenograft tumor model also confirmed the same results. Conclusion The achieved outcomes elucidate that CAFs can deliver piR-35462 containing exosomes to OSCC cells and promote OSCC progression via FTO/Twist mediated EMT pathways, and could represent a promising therapeutic target for OSCC.